Determinants of corporate capital structure: Evidence from Macedonian panel data - Biljana Jovanovic (National Bank of the Republic of Macedonia, 2015)
The purpose of this study is to analyze capital structure decisions of Macedonian companies by using firm level data for the period 2000-2014. More specifically the study is focused on two specific questions. First, by using dynamic panel methodology we try to identify the financial leverage determinants of Macedonian firms. Second, we analyze changes in firms' leverage decisions by comparing the post-crisis outcome with the pre-crisis determinants. Our results show that the size of the companies and growth opportunities are positively related to leverage, while profitability, tangibility and non-debt tax shield are negatively associated with leverage. Regarding the second question, the pre-crisis state of the theoretical determinants does not explain the post-crisis behavior of the Macedonian firms. On the other hand, the leverage decisions after the crisis were affected by the pre-crisis level of leverage and changes in firms' performance during the crisis.
Keywords: C33; G32; 330; Panel Data; Corporate Capital Structure; Pecking Order Theory; Trade-off Theory